PENERAPAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN PRESTASI BELAJAR SISWA - Yetti Apriani; Alexon Alexon (DIADIK, 2022)
This study aims to describe the application of CTL learning in improving critical thinking skills and student achievement and to describe the effectiveness of the application of CTL in improving student learning achievement in science subject content in class IV SD, Dempo Tengah Subdistrict, Pagaralam City. The research design used was classroom action research which consisted of 3 action cycles consisting of planning, implementing, observing and reflecting. This research also uses a quasi-experimental research method. The subjects of classroom action research (PTK) were grade IV even semester students of 2020/2021 SDN 35 Pagaralam, the sample of the experimental class was class IV SDN 40 Pagaralam and IV SDN 14 Pagaralam as the control class. The research instrument used observation sheets and tests. Based on the results of observations of students' critical thinking in cycle I, cycle II and cycle III, the average score of students has increased. The research data were analyzed using descriptive statistics, mean, percentage, and t-test. From the results of statistical calculations using the independent sample t test, obtained a significant increase in student achievement scores taught using CTL. The results showed that critical thinking and student learning achievement improved significantly by implementing CTL learning in class IV SD, Dempo Tengah Subdistrict, Pagaralam City